Intravascular lithotripsy for calcified coronary arteries in the real‐world: From rock to metal. Issue 2 (9th August 2021) - Seth, Ashok; Kumar, Vijay
Key Points: The safety and effectiveness of IVL has been demonstrated in DISRUPT CAD studies in selected severely calcified coronary lesion. 'Real‐world use' of IVL extends to more complex calcified lesions not evaluated in the above studies. Understanding best practices when using IVL ensures optimal outcomes for the patients.